Electron exchange model potential: Application to positronium-helium scattering - Biswas, P. K. [UNESP]; Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 1999)
The formulation of a suitable nonlocal model potential for electron exchange is presented, checked with electron-hydrogen and electron-helium scattering, and applied to the study of elastic and inelastic scattering and ionization of orthopositronium (Ps) by helium. The elastic scattering and the [Formula Presented] excitations of Ps are investigated using a three-Ps-state close-coupling approximation. The higher [Formula Presented] excitations and ionization of Ps atoms are treated in the framework of the Born approximation with present exchange. Calculations are reported of phase shifts and elastic, Ps excitation, and total cross sections. The present target elastic total cross section agrees well with experimental results at thermal to medium energies. © 1999 The American Physical Society.